Cross-cultural adaptation and validation of the Hospital Survey on Patient Safety questionnaire for a Chilean hospital - Paulina Hurtado-Arenas; Miguel R. Guevara; Victor M. González-Chordá (BMC, 2024)
Abstract Background Hospital Survey on Patient Safety version 2.0 (HSOSPS 2.0) from the Agency for Healthcare Research and Quality enables hospitals to gather the information needed to evaluate the patient safety culture within their institution. However, version 2.0 has not been widely implemented in Chile. This study aims to customize and validate the original HSOSPS 2.0 for a Chilean hospital. Methods Translation and cross-cultural adaptation, content validity through a group of experts, and a pilot test with cognitive pretest were applied to 259 participants from the nursing team in 11 hospital services to study construct validity and reliability. Results In the current study, a version of the questionnaire adapted to the Chilean cultural context showed excellent content validity with an index of 0.982 (S-CVI). After conducting exploratory factor analysis, a new model with 7 dimensions and 23 questions was proposed, down from the original 10 dimensions and 32 questions. This new model explains 71% of the variability. The model's goodness of fit indicators were CFI=0.995, TLI=0.994, and RMSEA=0.048. The results of McDonald's Omega showed high overall reliability with 0.9325. Conclusions This study provides a validated measurement instrument that contributes to improving patient safety conditions at the level of the hospital nursing team in highly complex establishments in Chile. However, the dimensions, such as the number of items, were reduced This questionnaire can be used in future nursing research by expanding the sample among health professionals in Chile. Relevance to clinical practice Applying this version of the questionnaire will be highly beneficial for clinical administrators and nursing staff. It will improve their care practices and promote patient safety in public hospitals in Chile, as well as assist in enhancing nursing policies.